Improvement of the microbiological quality of a beer filtration system - Branco, André dos Reis Santos Nápoles (2020)
This work addresses the improvement of the microbiologic quality of beer in the BBT (Bright Beer Tanks), after the filtration of green beer, which is the final step of beer production before packaging. The objective was to improve the KPI to achieve a 91.00% Micro BBT FTR indicator in the end of the team’s work, starting from 85.42% in the beginning of the work. A multidisciplinary improvement team inside the brewery was formed to study and implement changes that would improve the FTR (First-Time Right) Microbiology Indicator for the BBT. The designed team was routed in the TPM (Total Productive Management) structure of the brewery, using the 5S’s philosophy, and following a microbiological defect reduction route. The team improved the indicator up to 87.05% by the conclusion of its work, thus falling short of its goal. Despite this, several improvements were made, such as the removal of dead legs on the CIP Circuit and the creation of an integrated Cleaning, Inspection, Lubrication and Tightening plan. Besides this, important studies regarding BBT usage and beer recovery alternatives in filtration were also carried out, and these could have a very significant impact in the overall Micro BBT FTR in the future.